2010
DOI: 10.1002/hbm.20945
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute psychosocial stress on working memory related brain activity in men

Abstract: Acute psychosocial stress in humans triggers the release of glucocorticoids (GCs) and influences performance in declarative and working memory (WM) tasks. These memory systems rely on the hippocampus and prefrontal cortex (PFC), where GC-binding receptors are present. Previous studies revealed contradictory results regarding effects of acute stress on WM-related brain activity. We combined functional magnetic resonance imaging with a standardized psychosocial stress protocol to investigate the effects of acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
67
2
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 48 publications
9
67
2
3
Order By: Relevance
“…Also, the time of the day, the nature of the stressor and the memory tasks, the time spent in the laboratory before the stressor and possible interference with other tasks during the study can influence the direction of stress effects on memory. This may explain why some studies reported working memory to be decreased by stress (Elzinga and Roelofs, 2005;Luethi et al, 2008;Oei et al, 2006;Schoofs et al, 2008Schoofs et al, , 2009) whereas others observed increased function (Cornelisse et al, 2011;Duncko et al, 2009;Kuhlmann et al, 2005;Oei et al, 2009;Weerda et al, 2010). The current observations clearly indicate that when subjects are tested under conditions of MR blockadeFwhich arguably might shift the balance from MR activation toward GR activationFworking memory is impaired.…”
Section: Discussionmentioning
confidence: 50%
“…Also, the time of the day, the nature of the stressor and the memory tasks, the time spent in the laboratory before the stressor and possible interference with other tasks during the study can influence the direction of stress effects on memory. This may explain why some studies reported working memory to be decreased by stress (Elzinga and Roelofs, 2005;Luethi et al, 2008;Oei et al, 2006;Schoofs et al, 2008Schoofs et al, , 2009) whereas others observed increased function (Cornelisse et al, 2011;Duncko et al, 2009;Kuhlmann et al, 2005;Oei et al, 2009;Weerda et al, 2010). The current observations clearly indicate that when subjects are tested under conditions of MR blockadeFwhich arguably might shift the balance from MR activation toward GR activationFworking memory is impaired.…”
Section: Discussionmentioning
confidence: 50%
“…Our preclinical data may provide support for the contention that mood disorders and stressful life events are associated with abnormal Glu neurotransmission. Furthermore, the increased excitatory Glu level of the cerebral cortex and hippocampus of the rat brain revealed in our study could also underlie the acute stress-elicited changes in prefrontal and hippocampal activity revealed from several fMRI studies of human subjects [23,24]. Interestingly, the altered glutamatergic activity in the cerebral cortex (mainly including the prefrontal cortex) could not revert to its pre-stress state by the end of the recovery period, indicating that the acute strong stressor induced sustained potentiation of the glutamatergic activity even after the action of the stressful event was over.…”
Section: Discussionmentioning
confidence: 84%
“…It is possible that robust suppression of putative inhibitory interneurons during the delay interval contributes to the increased responsiveness of WS neurons weakly tuned to delay, whereas a global reduction in PFC gain could account for the generalized suppression of task-related activity during stress. Regardless of mechanisms underlying the stressrelated changes in neuronal activity patterns during the T-maze task, these observations provide a parsimonious explanation for the apparent discrepancy between pharmacological observations predicting a stress-related suppression of delay-tuned neurons (Arnsten 2009;Arnsten et al 2012) and electrophysiological and imaging observations indicating stress increases overall PFC activity during the delay interval of working memory tasks (Weerda et al 2010;Devilbiss et al 2012).…”
Section: Stress Actions In the Pfc Are Dependent On Neuron Response Smentioning
confidence: 91%
“…Results from pharmacological studies strongly predict that stress suppresses delay-related spiking activity via increased catecholamine receptor signaling (Arnsten 2009). Nonetheless, both human imaging and rodent electrophysiological measures of global neuronal activity indicate that stress increases delay-related PFC activity (Yuen et al 2009(Yuen et al , 2011Weerda et al 2010;Szalma and Hancock 2011;Devilbiss et al 2012), consistent with excitatory actions of stress-related glucocorticoids on PFC neurons (Yuen et al 2011). Beyond the coding of delay-related information, subpopulations of PFC neurons have been identified that encode both positive (reward) and negative (error) response/decision outcomes (Niki and Watanabe 1979;Ito et al 2003;Amiez et al 2006).…”
Section: Introductionmentioning
confidence: 99%